Effect Of Social Media Usage Patterns On Academic Performance And Psychological Well-Being Of Undergraduate Students - Khan, Sadia; Ullah, Saeed; Abbas, Muhammad Mansoor; Akhtar, Muhammad; Kaleem, Muhammad Faisal; Ali, Rashid (Migration Letters, 2024)
In the contemporary world, social media has become an integral aspect of human existence, exerting considerable influence in various ways. However, the excessive use of social media is associated with adverse effects on academic achievement and psychological well-being, contributing to heightened levels of anxiety, depression, loneliness, and low self-esteem. The primary objective of the study was to investigate the effect of social media usage patterns on the academic performance and psychological well-being of undergraduate students. The research employed a causal-comparative research design, also known as ex post facto research, with the objective of revealing causal relationships between variables. Employing a simple random sampling technique, 455 students were randomly selected as a sample. Respondents filled out a standardized questionnaire in order to assess their social media patterns. To assess the pupils’ psychological well-being, a psychological well-being questionnaire was utilized. Regression analysis and the Pearson correlation coefficient were used to analyze the data. The findings of the study indicate a strong negative relationship between psychological well-being, academic performance, and social media usage patterns. The findings also indicate that social media usage patterns significantly impact students’ academic performance and psychological well-being. These findings make a substantial contribution to the current body of knowledge and have implications for educational institutions.